STRATEGI PEMBELAJARAN KITABAH DALAM UPAYA PENINGKATAN KETERAMPILAN MENULIS BAHASA ARAB BAGI PESERTA DIDIK MADRASAH TSANAWIYAH - Ritonga, Mahyudin; Martias, Dian; Dani, Nishfu Rahma; Jumusti, Liza (Universitas Muhammadiyah Tangerang, 2023)
Learning foreign languages for Indonesians such as Arabic is still faced with serious problems, among the problems faced by students is the difficulty in writing Arabic. Therefore, the right strategy is needed in overcoming these problems, therefore this study aims to find our learning strategies used in madrasas. The research was conducted at MTs Negeri 1 Payakumbuh, the approach used was qualitative, data was collected with observation techniques, interviews and documentation studies. The result of the research is that the strategy used by the teacher is an alignment between all components of learning, namely systematic Arabic learning, learning methods are used in harmony with our learning materials, teachers improve existing media by making their own media that are in accordance with the character of students. The use of such learning strategies can improve the skills of learners in writing Arabic.